Perbandingan Hasil Pengolahan Data GPS Geodetic Menggunakan Aplikasi Compass Solution dan Aplikasi Trimble Business Center - Dawamul Arifin; Nadira Ayu Herliana; Feri Fadlin; Radik Khairil Insanu (Journal of Geomatics Engineering, Technology, and Science, 2024)
The background of this research is as an effort to determine the level of accuracy in the Compass Solution and Trimble Business Center software. So that you can find software with a better level of accuracy. The purpose of this study is to find out the results of processing static observation data using Compass Solution and Trimble Business Center software to obtain a report on the processing results in the form of point coordinate values. The methods used in measurement activities are absolute and differential methods which are then processed using Compas Solution Software and Trimble Business Center software. The results obtained in this study are the availability of the difference in coordinates X, Y and Z when processing using Compass Solution and Trimble Business Center software. The results of differential method data processing using the Trimbel Business Center application (strategy 3) are closest to the fixed BM coordinate values ​​that have been determined, namely with an average difference in the X value of 7.75 mm, Y value of 17.5 mm, and the average difference The Z value is 266.25 mm. Meanwhile, the results of absolute method data processing using the Compass Solution application (strategy 2) are closest to the fixed BM coordinate values, namely with an average difference in the X value of 1,129 mm, Y value of 229.25 mm, and an average difference in Z value is 1,131 mm.